Todas las sangres: A possible world - Félix Benites, Edwin (2021)
The purpose of this essay is to explain that the novel Todas las sangres is within the fictional statute. The analysis is based on the ideas presented by the participants in the second-round table, on June 23, 1965, organized by the Institute of Peruvian Studies. Literary critics described the work of José María Arguedas as a sociological work; instead, social scientists questioned that the novel was not a valid photograph to study and analyze the Peruvian reality. These sociological percepcions underestimated the esthetic quality and fictional character of literary work. That is, they confused the artistic representation of a possible world with a sociologic document that should reflect reality. Todas las sangres is a construction from a fictional statute that should not reflect reality in its strict sense, but what it should be.